The Influence of Perceived Usefulness Perceived Ease of Use and Perceived Risk on Interest in Using e-Wallets Among STIE AMM Mataram Students in The Digital Era - Indrawati, Laili; Fariantin, Erviva; Fajariah, Faizatul (Fakultas Agama Islam Universitas Islam Al-Azhar, 2024)
This study examined the effect of perceived usefulness, perceived ease of use, and perceived risk on interest in using e-wallets among STIE AMM Mataram students in the digital era. The population was e-wallet management students but the exact size was unknown. A purposive sample of 60 students was obtained through distributing questionnaires using Google Forms. Multiple linear regression analysis was used to analyze the data. The results showed the regression equation was Y = 2,142 + 0.274X1 + 0.190X2 -0.008X3, meaning interest in using e-wallets would be 2,142 if the independent variables did not change. Hypothesis testing revealed perceived usefulness and perceived ease of use significantly affected interest while perceived risk had a negative but insignificant effect. The independent variables could explain 51.6% of interest in use, while the remaining 48.4% was influenced by other factors. In conclusion, perceived usefulness and ease of use most impacted students' interest in using e-wallets